2018
DOI: 10.1016/j.ajog.2017.11.565
|View full text |Cite
|
Sign up to set email alerts
|

The role of aspirin, heparin, and other interventions in the prevention and treatment of fetal growth restriction

Abstract: Fetal growth restriction and related placental pathologies such as preeclampsia, stillbirth, and placental abruption are believed to arise in early pregnancy when inadequate remodeling of the maternal spiral arteries leads to persistent high-resistance and low-flow uteroplacental circulation. The consequent placental ischaemia, reperfusion injury, and oxidative stress are associated with an imbalance in angiogenic/antiangiogenic factors. Many interventions have centered on the prevention and/or treatment of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 125 publications
0
101
0
Order By: Relevance
“…In current practice, planned early birth is the only therapeutic option available that imposes further life‐long health risks. No current interventions alter fetal growth and wellbeing to allow safe prolongation of pregnancy, although a number of therapies are under investigation in a pipeline of preclinical and clinical studies aiming to modify the uteroplacental circulation and in utero environment . The most far advanced of these investigative therapies is the maternal administration of sildenafil citrate.…”
Section: Introductionmentioning
confidence: 99%
“…In current practice, planned early birth is the only therapeutic option available that imposes further life‐long health risks. No current interventions alter fetal growth and wellbeing to allow safe prolongation of pregnancy, although a number of therapies are under investigation in a pipeline of preclinical and clinical studies aiming to modify the uteroplacental circulation and in utero environment . The most far advanced of these investigative therapies is the maternal administration of sildenafil citrate.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding primary prevention strategies, recent meta‐analyses have demonstrated that aspirin modestly reduces the risk of delivering an SGA infant in women at high risk, with most benefit derived by starting treatment before 16 weeks of gestation and using a dose of ≥100 mg (risk ratio 0.56–0.76) . Patient selection of those at increased risk was primarily based on an increased risk of developing a hypertensive pregnancy disorder rather than delivering an SGA infant . Currently, there are no effective interventions for the primary prevention of LGA available, except for the treatment of women with GDM that indirectly lowers the risk of LGA, such as diet .…”
Section: Discussionmentioning
confidence: 99%
“…69,70 Patient selection of those at increased risk was primarily based on an increased risk of developing a hypertensive pregnancy disorder rather than delivering an SGA infant. 71 Currently, there are no effective interventions for the primary prevention of LGA available, except for the treatment of women with GDM that indirectly lowers the risk of LGA, such as diet. 24 In summary, the application of the currently available prediction models for the risk of SGA or LGA, in settings in which models for the identification of 'vascular' (pre-eclampsia)-and 'metabolic' (GDM)related complications are already applied, are not likely to result in additional benefit regarding the overlap of predictors and preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…(7,8) In obstetrics, low-dose aspirin has been shown to be effective in preventing preterm preeclampsia, with delivery at <37 weeks' gestation, in women at risk. (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) The ASPRE (27) The latest systematic review and meta-analysis demonstrated that the reduction in the rate of preterm preeclampsia was confined to the subgroup in which aspirin was initiated at ≤16 weeks' gestation and at a daily dose of ≥100 mg (relative risk [RR], 0.33; 95% CI, 0.19-0.57). (20) Evidence suggests that pre-conception or early administration of low-dose aspirin might improve endometrial growth, placental vascularization and organogenesis.…”
Section: Introductionmentioning
confidence: 99%